Assessment of Total Laboratory Errors in Clinical Chemistry Laboratory: Experience at a Tertiary Care Hospital - Syeda Sabahat Haider Zaidi; Mehvish Sana; Muhammad Tariq Ghafoor (Liaquat National Journal of Primary Care, 2022)
Background: Efficient Laboratory services are the backbone of the modern healthcare facility. 70% of all medical decisions are based on laboratory data. We need to assess errors in the testing process to reduce their negative effect on patient outcomes and the entire healthcare sector. Objective: To assess total laboratory errors in terms of pre-analytical, analytical, post-analytical in the clinical chemistry laboratory. Materials and Methods: This cross-sectional study was conducted in Clinical Chemistry Laboratory, Sheikh Zayed Hospital, Rahim Yar Khan from 1st January to 30th June 2021. All blood samples received in Chemical Pathology Section for routine chemistry analysis in 6 months were included in the study using a consecutive sampling technique. 61891 blood samples were assessed for the following pre-analytical errors: Hemolysis, icterus, lipemia, incorrect order of draw, insufficient quantity, wrong tube, mislabeled specimen, missed patient information. Analytical errors were a violation of westgard rules while post-analytical errors included uninformed critical results, prolonged turnaround time and data transcription errors. Urine and other body fluids such as cerebrospinal fluid (CSF), ascitic fluid, pleural fluid, pericardial fluid received for chemical analysis were excluded. Data analysis was done using SPSS 16. Results: Out of the total laboratory errors 5574(9%), pre-analytical errors were the most frequently occurring errors (80.95%) followed by post-analytical errors (18.25%) and analytical errors (0.80%). The most frequently occurring pre-analytical error was hemolysis (64.38% of 80.95%). The most frequently occurring post-analytical error was uninformed critical results (70.79% of 18.25%). Conclusion: Pre-analytical errors have the highest percentage in total laboratory errors followed by post-analytical errors. Errors in the analytical phase are less due to Internal Quality Control & laboratory automation